Sustainable construction: Public involvement in monitoring EMP implementation - Nurol Huda, Dahalan; Abdul Rahimi, Abdul Rahman; Saffuan, Wan Ahmad (Construction Industry Development Board (CIDB), 2023)
The importance of Environmental Management Plans (EMPs) in promoting sustainable construction practices cannot be overstated. These plans are crucial in minimising the environmental impact of construction activities and ensuring long-term environmental sustainability. In Malaysia, the construction sector has been facing the varying impacts of residential building construction on the ecosystem, natural resources, and the public, accounting for 67.5%, 21%, and 11.5%, respectively. Given the prevalence of construction projects in densely populated areas, residents living near these sites are particularly vulnerable to potential adverse effects, especially from earthwork and excavation activities.